THU0360 Small Bowel Mucosal Findings in Familial Mediterranean Fever. (10th June 2014) - Demir, A.; Akyüz, F.; Gokturk, S.; Evirgen, S.; Gulluoglu, M.; Erer, B.; Kamali, S.; Gul, A.
Abstract : Background: Familial Mediterranean fever (FMF), the most common form of autoinflammatory disorders, is characterized by recurrent episodes of serositis or arthritis. Abdominal pain due to peritoneal inflammation is the most common manifestation of FMF. However, other gastrointestinal manifestations including diarrhea can also be observed. No detailed investigation by endoscopic examination of small and large bowels has been reported so far in FMF. Objectives: This study aimed to investigate the gastrointestinal tract by endoscopy in FMF patients with peritoneal attacks and abdominal findings. Methods: The study group consisted of 41 patients with FMF, all fulfilling Tel-Hashomer criteria and followed-up at the Rheumatology Division. All of the patients were taking colchicine at highest tolerable doses of 1 to 2 mg/day. A standard questionnaire was used to record the gastrointestinal symptoms, other clinical findings, MEFV mutations, and history of medications including non-steroid anti-inflammatory drugs (NSAIDs). Gastroscopy, colonoscopy and small bowel capsule endoscopy (OMOM, Jinshan Science and Technology Company, China) were performed in all patients, and biopsies were taken from terminal ileum and duodenum. Results: The mean age of the patients was 34±11 years, 63% of them were female, and 67.7% of them were carrying MEFV exon 10 mutations. All patients had a history of abdominal attacks and experienced at least one peritonitis episode within the last two months. Only one patient used NSAIDs in addition to colchicine. In endoscopic investigations, gastric erosion was detected in only one patient, and no significant findings were detected in colonoscopy. Pathologic examination of the terminal ileum specimens revealed nonspecific chronic inflammation in 70% of the patients. Capsule endoscopy showed small bowel mucosal defects in 44% (erosions in 26.8%, ulcer in 17.1%) and edema in 29.3% of the patients. Most (64%) of the ulcer and erosions were localized to jejunum, and only 24% were in ileum. In one patient, images were compatible with infiltration in the distal jejunum, and reactive amyloidosis was confirmed by biopsy. No correlation was found between small bowel mucosal defects and MEFV variations, and no predictor was detected by multivariate analysis for mucosal defects. Conclusions: Capsule endoscopic investigations revealed small bowel mucosal defects in almost half of the patients with FMF, and it was mainly localized to jejunum. Those mucosal changes may result from underlying autoinflammatory condition or chronic exposure to colchicine. Further investigations are warranted for the characterization of small bowel findings and to rule out the possibility of colchicine toxicity. Acknowledgements: Funded by Istanbul University, Scientific Research Projects, IUBAP No: 27107. Disclosure of Interest: : None declared DOI: 10.1136/annrheumdis-2014-eular.5964